2020
DOI: 10.3390/foods9060809
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Toxicity and Genotoxicity of Polysaccharide Fraction from Young Barley Leaves (Hordeum vulgare L.)

Abstract: Polysaccharides isolated from various plants are considered precious bioactive materials owing to their potent biological activities. Previously, we prepared a polysaccharide fraction (BLE0) isolated from young barley leaves (Hordeum vulgare L.), demonstrating its anti-osteoporotic and immunostimulatory activities. However, data regarding BLE0 toxicity is lacking. To establish its safety, in vitro genotoxicity (chromosomal aberration and bacterial reverse mutation assays) and acute oral toxicity assays were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These elements include compositional analysis, chemical structure analysis, and toxicity studies [23]. Safety evaluations are critical when new compounds/foods are introduced to the marketplace [24,25]. In our preliminary studies, we elucidated two new lignans and isolated six known compounds from KP-1 that showed neuroprotective and anti-inflammatory effects [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…These elements include compositional analysis, chemical structure analysis, and toxicity studies [23]. Safety evaluations are critical when new compounds/foods are introduced to the marketplace [24,25]. In our preliminary studies, we elucidated two new lignans and isolated six known compounds from KP-1 that showed neuroprotective and anti-inflammatory effects [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Most active extracts derived from herbal medicines are considered safe, but some of them have known toxicities [ 35 , 36 ]. Therefore, the scientific evaluation and basis for the safety of extracts are considered important and essential [ 37 , 38 , 39 ]. The crude polysaccharides extracted from MOR have diverse pharmacological effects, which indicates great potential for applications in the development of new food raw material or functional food.…”
Section: Introductionmentioning
confidence: 99%
“…It holds great economic and medicinal value [29]. In past the members of the family Poaceae are investigated for phytochemicals screening [30], elemental analysis and antioxidant activity [31], proximate composition [32], genotoxic activity [33] and antidiarrheal activity [34]. There is no literature are present on pharmacognostic evaluation of the selected plant.…”
Section: Introductionmentioning
confidence: 99%